Analysis of the European Union's Lawsuit Against Indonesia Regarding the Ban on Nickel Ore Exports - Ilhan Pasha Islamy Trisnadi (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Nickel is a metal that has the characteristics of a silvery-white color with the characteristics of strength, heat resistance, light weight and corrosion resistance with the chemical formula Ni. It has good electrical and thermal conductivity making it suitable for coating copper, iron and aluminum to prevent corrosion. Nickel was first discovered and developed by Cronstedt in 1751, in a mineral called Nicolite (Kupfernickel), which was found in the Sudbury region, Ontario, Canada, a nickel-producing area of 30% of the world's demand for nickel metal. One of the countries with the largest nickel reserves is Indonesia. According to several experts, it is estimated that Indonesia has nickel reserves of more than 1 billion tons of nickel. The largest distribution of nickel reserves is in the eastern part of Indonesia. The distribution of nickel in Indonesia and the distribution of nickel mining in Indonesia today, among others, are found on the islands of Sulawesi (Southeast and South Sulawesi), Maluku and Papua. Unfortunately, currently a lot of Indonesian nickel is exported in the form of raw material, so the selling price is very cheap. Thus, government support is very much needed to improve nickel processing, such as support for ease of licensing, clear and transparent rules and regulations. This support can be seen in the issuance of a decree by the Ministry of Energy and Mineral Resources Number: 549.Pers/04 SJI/2019 dated 2 September 2019 concerning "Nickel Ore Cannot be Exported Again as of January 2020".